Heterozygous frameshift mutation in FaMYB10 is responsible for the natural formation of red and white-fleshed strawberry (Fragaria x ananassa Duch) - Yuan, Huazhao; Cai, Weijian; Chen, Xiaodong; Pang, Fuhua; Wang, Jing; Zhao, Mizhen (Frontiers in Plant Science, 2022)
During natural evolution and artificial selection, the fruit color of many species has been repeatedly gained or lost and is generally associated with mutations in genes encoding R2R3-MYB transcription factors, especially MYB10. In this study, we show that a heterozygous frameshift mutation (FaMYB10AG-insert/FaMYB10wild) is responsible for the loss of anthocyanins in the flesh of cultivated strawberry. Comparative transcriptomic and metabolomic analyses of red- and white-fleshed strawberry indicated that the low expression level of FaUFGT (flavonol-O-glucosyltransferases) was responsible for the loss of anthocyanins and accumulation of proanthocyanidin in the white-fleshed strawberry and was the crucial gene that encodes enzymes of the anthocyanin biosynthesis pathway. Accordingly, overexpression and silencing of FaUFGT altered anthocyanin content and changed the flesh color of strawberry fruits. Furthermore, whole-genome resequencing analyses identified an AG insertion in the FaMYB10 coding region (FaMYB10AG-insert) of white-fleshed strawberry. Y1H and EMSA assays showed that FaMYB10wild was able to bind to the promoter of the FaUFGT gene, while the FaMYB10AG-insert could not. The skin and flesh color were tightly linked to the number of fully functional FaMYB10 copies in the selfing progeny of white-fleshed strawberry. Our results suggested that heterozygous frameshift mutation of FaMYB10 resulted in the loss of the ability to activate the expression of the FaUFGT gene, was responsible for the natural formation of red and white-fleshed strawberry.